PENGARUH TEAT DIPPING MENGGUNAKAN EKSTRAK BUNGA CENGKEH (Syzygium aromaticum) TERHADAP RASA, AROMA, DAN WARNA SUSU SEGAR (Teat dipping effect used clove flower extract (Syzygium aromaticum) on taste, aroma, and color of fresh milk) - Danes Suhendra; Abiyoga Rizal Adhitama; Martha Arum Nugraheni; Labib Abdillah (Universitas Nusa Cendana, 2023)
Bacterial contamination can reduce physical quality of milk by changing color, aroma, and taste. Teat dipping can be one of attempt reduce physical quality loss affected by bacterial contamination. Chemical synthetic solution as teat dipping leaving residue in milking yields. The attempt to reducing residue are by using herbal material for dipping solution. This study aims to analyze the effect of dipping used clove flower extract (Syzygium aromaticum L.) on the color, aroma, and taste of fresh milk. Research method are used experimental method with complete randomize design (CRD) with single factor and 5 replications. The treatment in this study were without dipping treatment (P0), dipping with a concentration of 5% clove flower extract (P1), dipping with a concentration of 10% clove flower extract. % (P2), and dipping with a concentration of 15% clove flower extract (P3). Organoleptic test was carried out by 30 panelists. Data analysis used descriptive analysis method with the help of SPSS 26 to find out the description of the organoleptic test data. The results of this study indicate that the dipping treatment did not change the color, aroma, and taste of fresh milk. Fresh milk were at its normal level and does not left the typical clove residue. Conclusion of this research is clove flower extract can used as dipping solution because does not leaving residue so didn’t changed color, aroma and taste of milk.